Drobna wytwórczość jako element rynku nabywcy - Gawrzyński, Janusz (Wydział Prawa i Administracji UAM, 1966)
The buyer's market is mostly defined as a situation in which the supply exceeds the demand. Recent works introduce to this notion a new moment, that of a constant influence exerted by buyers on suppliers. The degree of the buyer's influence on the activities of various links of the transaction chain — especially those which are situated close to consumption — is of considerable importance. In the exchange process such a situation exists in regard to the majority of small producers. Therefore it seems justified to undertake an analysis of the function of small producers' sector as an element of the buyer's market. In the system of socialist economy the creation of that sector is based on social as well as economic premises. There are fundamental differences (in size, employment, technical equipment, volume of production a.s.o.) between centrally administered enterprises and the small producers' enterprises. The short series of production and its individualization are propitious to the elasticity of supplies, allowing for an easier adaptation to the changing and evermore diversified demand. All this is possible due to greater share of live labour than that of capital equipment in machines and tools and finally to more universal qualifications of workers. The greater part of goods and a substantial part of services of the sector of small producers are bought directly or indirectly by population. Thus the circle of buyers as well as of sellers is an important one — what in turn constitutes the premise of that particular market. The multitude of sellers (producers) in strictly defined conditions inclines to competition in the field of quality of goods and services and also in respect with prices. The sector of small producers is closely tied to the organs of the regional national councils. That subordination facilitates rational administration, the development of regional economy and the functioning of the regional and local market.